Detection of genetic variation affecting milk coagulation properties in Danish Holstein dairy cattle by analyses of pooled whole-genome sequences from phenotypically extreme samples (pool-seq). Issue 4 (1st April 2016) - Bertelsen, H. P.; Gregersen, V. R.; Poulsen, N.; Nielsen, R. O.; Das, A.; Madsen, L. B.; Buitenhuis, A. J.; Holm, L.-E.; Panitz, F.; Larsen, L. B.; Bendixen, C.
ABSTRACT: Rennet-induced milk coagulation is an important trait for cheese production. Recent studies have reported an alarming frequency of cows producing poorly coagulating milk unsuitable for cheese production. Several genetic factors are known to affect milk coagulation, including variation in the major milk proteins; however, recent association studies indicate genetic effects from other genomic regions as well. The aim of this study was to detect genetic variation affecting milk coagulation properties, measured as curd-firming rate (CFR) and milk pH. This was achieved by examining allele frequency differences between pooled whole-genome sequences of phenotypically extreme samples (pool-seq).. Curd-firming rate and raw milk pH were measured for 415 Danish Holstein cows, and each animal was sequenced at low coverage. Pools were created containing whole genome sequence reads from samples with "extreme" values (high or low) for both phenotypic traits. A total of 6, 992, 186 and 5, 295, 501 SNP were assessed in relation to CFR and milk pH, respectively. Allele frequency differences were calculated between pools and 32 significantly different SNP were detected, 1 for milk pH and 31 for CFR, of which 19 are located on chromosome 6. A total of 9 significant SNP, which were selected based on the possible function of proximal candidate genes, were genotyped in the entire sample set ( n = 415) to test for an association. The most significant SNP was located proximal to CSN3, explaining 33% of the phenotypic variance. CSN3, coding for κ-casein, is the most studied in relation to milk coagulation due to its position on the surface of the casein micelles and the direct involvement in milk coagulation. Three additional SNP located on chromosome 6 showed significant associations explaining 7, 3.6, and 1.3% of the phenotypic variance of CFR. The significant SNP on chromosome 6 were shown to be in linkage disequilibrium with the SNP peaking proximal to CSN3 ; however, after accounting for the genotype of the peak SNP within this QTL, significant effects ( P -value < 0.1) could still be detected for 2 of the SNP accounting for 2 and 1% of the phenotypic variance. These 2 interesting SNP were located within introns or proximal to the candidate genes—solute carrier family 4 (sodium bicarbonate cotransporter), member 4 ( SLC4A4 ) and LIM and calponin homology domains 1 ( LIMCH1 ), respectively—making them interesting targets for further analysis.